2020
DOI: 10.19177/rgsa.v9e02020532-552
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência Energética De Envoltória: Comparação Dos Métodos De Avaliação RTQ-C E Ini-C Através De Estudo De Caso

Abstract: Este artigo apresenta a aplicação da Etiqueta Nacional de Conservação de Energia – ENCE, do Programa Procel Edifica, para avaliar uma edificação de uso público da cidade de Joinville/SC, considerando o critério parcial de envoltória. Para tal, dispõe de duas metodologias, a primeira baseada no Regulamento Técnico de Qualidade para edifícios comerciais, de serviço e públicos (RTQ-C), método vigente para obtenção da Etiqueta, e a segunda na Instrução Normativa Inmetro (INI-C), uma proposta de atualização do méto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Despite the advancements in energy efficiency assessment, some studies have shown difficulties in applying the methods of RTQs and INIs (Gomes, 2017;Leite;Hackenberg, 2020;Muta, 2022). The data acquisition process is laborious and time-consuming, and the fragmented stages of the conventional design process exacerbate the situation (e.g., 2D documentation, and communication gaps).…”
Section: Energy Efficiency Labeling Of Buildings In Brazilmentioning
confidence: 99%
“…Despite the advancements in energy efficiency assessment, some studies have shown difficulties in applying the methods of RTQs and INIs (Gomes, 2017;Leite;Hackenberg, 2020;Muta, 2022). The data acquisition process is laborious and time-consuming, and the fragmented stages of the conventional design process exacerbate the situation (e.g., 2D documentation, and communication gaps).…”
Section: Energy Efficiency Labeling Of Buildings In Brazilmentioning
confidence: 99%